ESG criteria in green rebuilding of Ukraine - Kryvomaz, Tetiana I.; Chaliy, Ivan H.; Hamotskyi, Roman O.; Ilchenko, Igor S.; Tsyba, Artem M. (Kyiv National University of Construction and Architecture, 2023)
The historical retrospective of the construction industry shows a tendency to move to a qualitatively new level after crises and global upheaval. Global markets are currently being reformatted to reflect new investment priorities, where environmental, social and governance (ESG) criteria are gaining essential importance, and Ukraine is at the center of global transformations. Ukraine's post-war reconstruction plans include the use of green innovative technologies, as the formation of a green economy is the basis of the European Union Association Agreement. The concept of "green recovery" has become widespread, as investments in low-carbon technologies strengthen the country's resilience. Implementation of green building principles saves resources and energy, stimulates innovation and competitiveness, and increases the confidence of investors and increasingly conscious consumers. Current international trends are moving towards global decarbonization of the world economy and the widespread implementation of ESG non-financial reporting standards to screen and increase transparency of business. The construction sector plays a key role in achieving the Sustainable Development Goals, given the significant economic, environmental and social impacts of the construction industry. The requirements for decarbonization, safety and well-being of buildings are growing, and the increasing volume and complexity of data requires new tools and approaches. The application of ESG principles involves the creation of long-term sustainable value in the interests of the company and its stakeholders. In the construction sector, ESG factors are crucial for determining the overall value and potential of a property, which helps investors to obtain more information for decision-making and risk assessment. The use of (ESG) indicators ensures transparency, objectivity and measurability of the company's performance. Businesses that demonstrate concrete commitments to sustainable development will become undisputed leaders in their industries in the next 30 years and will gain access to investment capital. On the other hand, companies that do not take care of compliance with international standards in a timely manner risk losing business in the medium term.